Widow’s pension and cohabitation more uxorio: domestic partnership and registered partnership (decision of the higher Court of Castilla y León of December 10, 2018) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
A Uruguayan national is denied the widow’s pension due to dead of her co-habiting partner, also Uruguayan. They have been living together during twenty five years, and they had daughter, who was born in Uruguay. The partnership was not registered neither was certified in a public deed, as required by the Spanish social security legislation in order to be entitled to a survivor’s pension. The applicant seeks the application of her national law, that doesn’t have these requirements. The Court rejects the request considering that these requirements have constitutive nature. This constitutive nature is used by the Spanish courts for distinguishing between unmarried partner formal and unmarried partner factual.
Keywords: widow’s pension; private international law; unmarried couples/life partners; registration; notarial deed